PENGEMBANGAN BUDAYA ORGANISASI UNTUK MENINGKATKAN KEMANDIRIAN DOSEN DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA - NURUDDIN PRIYA BUDI SANTOSO (JURNAL MITRA SWARA GANESHA, 2014)
Nuruddin Priya Budi Santoso. Â Culture devolepment organization to increase self teacher in the Faculty of Teaching and Education University Tunas Pembangunan Surakarta. This study aims (1). To find a variety of organizational culture that has built up in FKIP UTP. (2). To find cultures that increase the independence in lecturer FKIP UTP. The method used in this study is a qualitative research, with research and development, with a model of the development of conceptual and procedural. The three stages of the research as follows: a preliminary study and design of a hypothetical model of the design through a survey and literature review, development and testing of the initial model rationally by the team. The subjects of the study is a lecturer within the Faculty of Teaching and Devolepment University Tunas Pembangunan Surakarta. While data collection techniques using interviews, observation, documentation, questionnaires and tests. Techniques analisia interactive data analysis by Miles and Hiberman (1984) (in Lexy J. Moleong, 2001: 50). The analytical model has three components, namely data reduction, data analysis and conclusion. The study concluded: 1 organizational culture has been awakened in Faculty of Teaching and Devolepment University Tunas Pembangunan Surakarta , it can be seen that the lecturers have to know and understand the organization's management system is based on the vision, mission, goals and objectives and strategies to achieve within the Faculty of Teaching and Devolepment University Tunas Pembangunan Surakarta. 2 Independence of lecturers working in the organizational culture within the Faculty of Teaching and Devolepment University Tunas Pembangunan category based on criteria including a high score is an average of 191.46